Caracterização hidrogeológica do entorno do Centro Nacional de Pesquisa de Milho e Sorgo (CNPMS), em Sete Lagoas, MG - Rita de Cassia Rosado Batista (2009)
The objective of this study was to make a hydrogeological characterization of the surroundings of the Centro Nacional de Pesquisa de Milho e Sorgo (CNPMS), a research site located at the outskirts of the city of Sete Lagoas MG, and managed by the Empresa Brasileira de Pesquisa Agropecuária (Embrapa). The hydro-geological characterization aims at guiding activities for evaluation projects of the transportation of infecting elements in the soil and in the underground water. It is important to emphasize that the hydrogeological studies which has been developing by many authors in the same area, indicate that the local geology is composed basically by carbonate rocks upon deposites over the crystalline basement. Therefore, the groundwater exploitation in the region occurs mainly in the carbonate aquifers. Initially, to promote the hydrogeological characterization here proposed, a collection of dataabout the region was made. This collection involved several campaigns of field for the recognition and mapping of the water bodies existing in the area. Besides, the bibliographic review and the register of available information through public databases and digitalization of thematic existing maps were essential in this hydrogeological characterization process in the surroundings of CNPMS. From the data collected in this initial stage, a conceptual hydrogeological model of the areawas proposed, identifying the main hydrostratigraphic units and the flow conditions which were adapted to the computational hydrogeological model created with the help of the computer application Visual ModFlow.The computational simulation presented results within the expectation in terms of directions of flow lines and definition of dry and wet areas, apart from calibration data inside an acceptable margin of error for hydrogeological models. After calibrated, the computational model was used to simulate several present and future sceneries, presenting as values results of capacity of wells production, flows of spring andcapture zones of wells, cisterns, springs and ponds which might help in the management and protection of these hydric resources.